Il “progetto Palmira” (Siria) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
A new research program, in which the Università degli Studi of Milan (Italy) and the General Directorate of Antiquities and Museums of Syrian Arab Republic are involved, has begun in 2007 in Palmyra. The research aims at the investigation of the central south-western quarter of Palmyra, in the sector between the Agorà in the south-east, the late roman wall in the south /south-west, the Third Transverse Street and the Upper Great Colonnade Street in the north-west and in the north-east.Enclosed inside three columned streets and included inside the late antique town walls, this area is traditionally well known as “residential area”. In spite of its centrality in the urban texture – till today left out by systematic and deepened excavation activities - it doesn’t seem to contain monumental public or religious buildings; so it’s reasonable to suppose a prevalent, or even exclusive, residential destination but it’s necessary to verify these suppositions through a close scientific archaeological research.
Keywords: Syria; Palmyra; town-planning; residential area; italian-syrian mission; excavation